Estimation and prediction of time-varying GARCH models through a state-space representation: a computational approach. Issue 12 (13th August 2017) - Ferreira, Guillermo; Navarrete, Jean P.; Rodríguez-Cortés, Francisco J.; Mateu, Jorge
ABSTRACT: We propose a state-space approach for GARCH models with time-varying parameters able to deal with non-stationarity that is usually observed in a wide variety of time series. The parameters of the non-stationary model are allowed to vary smoothly over time through non-negative deterministic functions. We implement the estimation of the time-varying parameters in the time domain through Kalman filter recursive equations, finding a state-space representation of a class of time-varying GARCH models. We provide prediction intervals for time-varying GARCH models and, additionally, we propose a simple methodology for handling missing values. Finally, the proposed methodology is applied to the Chilean Stock Market (IPSA) and to the American Standard&Poor's 500 index (S&P500).